Development Of Miniature Base Transceiver Station Using Radio Frequency Energy Harvesting - Indra, Win Adiyansyah; Ismail, Nurin Alya; Manap, Zahariah; Saptari, Adi (Medwell Publications, 2020)
This study developed miniature of base transceiver station powered up by radio frequency energy harvesting. Base transceiver station is one of the major equipment in telecommunication system that able to transmit the signal to the receiver such as mobile phones which let it to complete the communication process. However, the base station need to have power supply to powered up the equipment. Previously studied, the base station’s power supply was from nature sources such as solar energy or wind energy. Due to the unstable condition of the weather, the power radiated might not be able to power up the base station hence, RF energy harvested was introduced. There are 3 main objectives of the project, firstly is to develop the basic concept of base transceiver station with radio frequency energy harvesting. Second, to implement the hall effect sensor into the concept of the base transceiver station. Third, to analyze the idea of the miniature of base transceiver station by look through the output and radio frequency energy harvesting. The RF energy harvested shows one of the methods to overcome this problem. RF energy harvested are one of the tools that need low frequency signal for it to transmit the power to the base transceiver station. The LEDs as the output which indicated as the antenna on the base transceiver station lights up as the hardware connection being made. Hence, the circuit for the RF energy harvesting and the hall sensor effect that will light up the LEDs shown. This study will show the implementation of the RF energy harvesting to the equipment.